An experimental investigation of magnetorheological (MR) fluids under quasi-static loadings - Mazlan, Saiful Amri (Trans Tech Publications, 2011)
In our earlier work, test equipment has been designed, simulated and fabricated to perform experiment on MR fluids in squeeze mode. Preliminary results were gathered and presented for the purpose of validating the test equipment. Therefore, in this paper, a further systematic investigation of MR fluids in squeeze mode has been carried out. As a result, MR fluids experienced rheological changes in three stages during compression and tension. Fluid-particles separation phenomenon was the main caused for the unique behaviour of MR fluids. Particle chains depended on the structure transformation in which the carrier fluid movement can be controlled by changing the magnetic field strength.